Extracellular Vesicles as Biomarkers of Acute Graft-vs.-Host Disease After Haploidentical Stem Cell Transplantation and Post-Transplant Cyclophosphamide - Lia, Giuseppe; Di Vito, Clara; Bruno, Stefania; Tapparo, Marta; Brunello, Lucia; Santoro, Armando; Mariotti, Jacopo; Bramanti, Stefania; Zaghi, Elisa; Calvi, Michela; Comba, Lorenzo; Fascì, Martina; et al. (Frontiers in Immunology, 2022)
High-dose post-transplant cyclophosphamide (PTCY) was initially introduced for graft-versus-host disease (GvHD) prevention in the setting of HLA-haploidentical transplantation. However, both acute and chronic GvHD remain a major clinical challenge. Despite improvements in the understanding of both acute and chronic GvHD pathogenesis, biomarkers that may reliably predict their onset have not yet been identified. We recently studied the potential correlation of extracellular vesicles (EVs) with the onset of acute (a)GvHD in transplants from related and unrelated donors. In the present study, we further investigated the role of the expression profile of membrane proteins and of the microRNA (miRNA) cargo (miRNA100, miRNA155 and miRNA194) of plasma EVs in predicting the onset of aGvHD in the setting of haplo-identical transplants with PTCY. Thirty-two patients were included. The expression profile, by flow-cytometry techniques, and the miRNA cargo, by Real-Time PCR analysis, were evaluated at baseline prior to transplant and at different time-points after transplant. By logistic regression analysis and Cox proportional hazard models, a significant association of the expression profile of antigens such as CD146, CD31, CD140a, CD120a, CD26, CD144, and CD30, and the miRNA cargo, with the onset of GvHD was observed. Moreover, we also investigated a potential correlation between EVs expression profile and cargo, with plasma biomarkers (ST2, sTNFR1, and REG3a) previously correlated with aGVHD. The triplet combinations of CD146, sTNFR1, and miR100 or miR194 strongly correlated with the onset of aGvHD (AUROC>0.975). A large prospective multicenter study is currently in progress to validate our findings.